Shear Velocity Model of Alaska Via Joint Inversion of Rayleigh Wave Ellipticity, Phase Velocities, and Receiver Functions Across the Alaska Transportable Array. Issue 2 (3rd February 2020) - Berg, Elizabeth M.; Lin, Fan‐Chi; Allam, Amir; Schulte‐Pelkum, Vera; Ward, Kevin M.; Shen, Weisen
Abstract: Through the Alaska Transportable Array deployment of over 200 stations, we create a 3‐D tomographic model of Alaska with sensitivity ranging from the near surface (<1 km) into the upper mantle ( 140 km). We perform a Markov chain Monte Carlo joint inversion of Rayleigh wave ellipticity and phase velocities, from both ambient noise and earthquake measurements, along with receiver functions to create a shear wave velocity model. We also use a follow‐up phase velocity inversion to resolve interstation structure. By comparing our results to previous tomography, geology, and geophysical studies we are able to validate our findings and connect localized near‐surface studies with deeper, regional models. Specifically, we are able to resolve shallow basins, including the Copper River, Cook Inlet, Yukon Flats, Nenana, and a variety of other shallower basins. Additionally, we gain insight on the interaction between the upper mantle wedge, asthenosphere, and active and nonactive volcanism along the Aleutians and Denali volcanic gap, respectively. We observe thicker crust beneath the Brooks Range and south of the Denali fault within the Wrangellia Composite Terrane and thinner crust in the Yukon Composite Terrane in interior Alaska. We also gain new perspective on the Wrangell Volcanic Field and its interaction between surrounding asthenosphere and the Yakutat Terrane. Key Points: We present a 3‐D shear velocity model of Alaska with constraint from near surface, via Rayleigh ellipticity (H/V), to upper mantle We explore interaction of upper mantle wedge and asthenosphere and impact on volcanism in the Aleutians and the Denali volcanic gap Basin structure throughout Alaska, including Colville Basin and Cook Inlet, is consistent with previous geophysical studies